Determinants of delayed onset of lactogenesis II among women who delivered via Cesarean section at a tertiary hospital in China: a prospective cohort study - Weining Lian; Juan Ding; Tiantian Xiong; Jiandi Liuding; LinTao Nie (BMC, 2022)
Abstract Background Cesarean birth is associated with a higher prevalence of delayed onset of lactogenesis II (DOLII) than vaginal birth. DOLII refers to the delayed initiation of copious milk production beyond 72 h after birth. This study aimed to determine the prevalence of, and factors associated with, DOLII among women who delivered via Cesarean section in China. Methods This prospective longitudinal cohort study recruited 468 women who delivered via Cesarean section at a tertiary hospital in China from 9 October 2021 to 17 May 2022. Face-to-face interviews were conducted during their delivery hospital stay to obtain information about demographic, medical, and breastfeeding factors. We assessed the onset of lactogenesis on postpartum day four, based on the maternal perception of changes in breast fullness. The Edinburgh Postnatal Depression Scale (EPDS) was used to screen for postpartum depression. Women with DOLII were interviewed via telephone or WeChat daily for one week postpartum to determine the timing of the onset of lactogenesis II. Univariate and multivariable logistic regression analyses were used to identify the determinants of DOLII. Results DOLII was experienced by 156 of 468 participants (33.3%). After adjusting for potential confounders, the odds of DOLII were 95% higher in primiparous women than multiparous women (adjusted odds ratio [aOR] 1.95; 95% confidence interval [CI] 1.29, 2.98), 75% higher in women with a serum albumin concentration < 35 g / L than women with normal serum albumin concentrations (aOR 1.78; 95% CI 1.09, 2.99), increased by 2.03-fold in women with an EPDS score ≥ 10 than women with an EPDS score < 10 (aOR 2.03; 95% CI 1.35, 3.07), and decreased in women with a higher number of breastfeeding sessions in the first 48 h postpartum (aOR 0.88; 95% CI 0.83, 0.93). Conclusions One-third of women with Cesarean section delivery experienced DOLII. DOLII was more likely in women who were primiparous, had a serum albumin concentration < 35 g / L, had a lower frequency of breastfeeding sessions, and had an EPDS score ≥ 10. Women with these risk factors who deliver via Cesarean section may need early breastfeeding support to ensure successful lactation.